The Development of Panjiasia Book based on Augmented Reality to Strengthen Pancasila Values for Children in Early Childhood Education - Lion, Eddy; Triyani, Triyani; Ananda, Kartika (Faculty of Humanities, Universitas Jenderal Soedirman, 2023)
This research aims to develop a PANJIASIA book based on augmented reality that is able to bridge young children to know, understand, internalize and apply the values ​​of Pancasila in everyday life. This research uses the type of research and development (Research and Development) with research stages 1) the initial survey in the field was taken based on data on the needs of PAUD teachers in instilling Pancasila values ​​in early childhood; 2) Prototype FGD; 3) Development of Augmented Reality-based PANJIASIA Books and prototype workshops; 4) validation of the PANJIASIA Book by validation of media experts and material experts; 5) Implementation of the PANJIASIA Book begins with small scale implementation and large scale implementation; 6) Publication and dissemination of the PANJIASIA Book to PAUD teachers in the Watershed (DAS) of Palangka Raya City. The results of this study, namely based on the results of the responses of PAUD teachers in FGD activities, showed a figure of 96%, which means that the quality of the products being developed is very feasible to be applied in the implementation of Pancasila learning. In addition, based on the validator's assessment, it shows a figure of 86%, which means that the product being developed is valid and feasible to use. Based on the results of small-scale and large-scale implementation, the results show that students are enthusiastic about learning Pancasila using books that have been developed because they are integrated with Augmented Reality technology.